Penerapan Model Ragam Taktik Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa Pada Materi Pengukuran Berat Benda Di Kelas II SDN 5 Guntung Manggis - Umu Khulsum; Herti Prastitasari (CV. ITTC INDONESIA, 2023)
The problem in this study is the low learning activity and mathematics learning outcomes in grade II students of SDN 5 Guntung Manggis. The problem is caused; 1) Learning focuses on teachers, 2) learning models that are less diverse. For this reason, improvements have been made with the RAGAM TAKTIK learning model. The purpose of this study is to analyze teacher activity, student activity and student learning outcomes. Classroom Action Research (PTK) was used in this study. The subjects of this study were 27 grade II students of SDN 5 Guntung Manggis. Qualitative and quantitative data were used in this study. Qualitative data are obtained from observations of teacher activity and student activity. These are quantitative data through classical percentages of student activity and student learning outcomes obtained from tests in groups and individuals. The results of this study showed that the teacher's activities in session IV met the criteria of